Perspektif Budaya dalam Studi Budaya Perusahaan: Peluang dan Perkembangan Penelitian di Indonesia: Cultural Perspectives in Corporate Culture Studies: Research Opportunities and Developments in Indonesia - Yuli Nugraheni; Ratih Puspa (Society, 2023)
This article examines how cultural perspectives have emerged and shifted the managerial perspective in studying corporate culture. There is no single approach to understanding organizational culture, as many factors influence its formation. The shift from functional to symbolic approaches is viewed as a form of resistance. A qualitative approach, employing literature review methods, is used in this study to view organizations as cultures and to see communication as a cultural performance. The study explores the opportunities and developments of corporate culture studies in Indonesia. By outlining these aspects, the article aims to contribute to the enrichment of organizational culture literature. This work is expected to enhance research and studies on organizational culture in Indonesia and provide a comprehensive view of the emergence of cultural perspectives in corporate culture studies. The author believes there are numerous opportunities for developing corporate culture studies in Indonesia, alongside the paradigm shift in evaluating corporate culture not only from a managerial perspective but also from a broader cultural perspective.